Building a Learning Organization in the Digital Era: A Proposed Model for Vietnamese Enterprises - Tuyen, Bui Quang (International Review of Management and Marketing, 2021)
In the context of the digital era, building a learning organization has become a strategy for enterprises to gain sustainable competitive advantages. This study proposes a model of learning organization in the digital era for Vietnamese enterprises. The model is developed based on existing literature of learning organization and the context of human resource development in Vietnamese enterprises. It is argued in this study that the utilization of technology which is added in the model of the learning organization as the fourth element, will play a critical role in the learning organization model in the digital era. Some implications for using the proposed model are also presented as suggestions for future research. Keywords: Human resource development, learning organization, organizational learning, digital era, Vietnamese enterprise. JEL Classifications: M50, M53, O32 DOI: https://doi.org/10.32479/irmm.11314